Skeletal muscle, neuromuscular organoids and assembloids: a scoping review - Jiang-li Yang; Shi-yan Qian; Min-li Chen; Li-xiang Wang; Yu Wang; Jing-jing Liu; Chen-shi Xi; Yu-xin Yang; Yue Li; Chong Gao; Guo-qing Zheng (EBioMedicine)
Summary: Skeletal muscle organoids (SKMOs), neuromuscular organoids (NMOs), and assembloids have emerged as powerful in vitro models that simulate the intricate cellular interactions between muscle and nerve, offering a promising approach to study function, development, and disease at the neuromuscular junction (NMJ). Given the relevance of NMJ dysfunction in diseases such as amyotrophic lateral sclerosis (ALS), these models provide insights into disease modelling. Scoping reviews are particularly valuable when exploring broad or emerging areas, as they help identify key concepts and evolving methodologies. Here, we conducted a scoping review by searching five databases, ultimately including 17 studies focussing on the development and application of SKMOs, NMOs, and assembloids in muscle function modelling. We highlight recent advancements and summarise various differentiation protocols, primarily utilising the Wnt signalling pathway agonist CHIR99021 and basic fibroblast growth factor (bFGF) to induce pluripotent stem cells into 2D neuromesodermal progenitors, further differentiated into SKMOs, NMOs, and assembloids. We also reviewed their cellular compositions, including motor neurons, neural stem cells, terminal Schwann cells, and astrocytes, alongside related research outcomes. Additionally, we discuss key challenges such as iPSC donor selection, standardisation, vascularisation, and 3D organoid imaging. This scoping review provides a foundation for future research on muscle function modelling.